Biochemical Composition and Digestive Enzyme Activity of Anguilla bicolor McClelland 1844 on Reproductive Phase - Rachmawati, Farida Nur; Susilo, Untung; Hana, Hana (Molekul, 2025)
ABSTRACT. The critical problems in eel cultivation are slow growth due to low digestibility and high feed conversion. This shows the need to understand the biochemical composition of eel to obtain information about the physiological condition, energetic adaptation, habits, nutritional value, and industrial uses. Nutritional data are also essential to develop a suitable processing method that enables eel to be consumed throughout the year while respecting state-imposed limitations to protect the species. Despite the significant contribution, there has been no data about the biochemical composition and the digestive enzyme activity of eel species such as Anguilla bicolor McClelland 1844, during the reproductive phase. Therefore, this study aimed to evaluate the biochemical composition of A. bicolor McClelland and the digestive enzyme activity during the reproductive phase. The experiment was conducted through a survey on eels in the reproductive phase with an average weight and length of yellow (106.00 ± 38.1 g and 42.00± 5.78 cm) and silver eel (362.89 ± 88.93 g and 59.86 ± 7.39 cm) respectively. The results showed that Nitrogen Free Extract (NFE) did not substantially alter between different phases, while the percent protein, lipid, ash, and fiber had significant variation (p<0.05). The activity of pepsin differed in various phases (p<0.05), while the activity of trypsin, amylase, and lipase of A. bicolor did not vary (p>0.05). The yellow eel had a higher body protein composition and pepsin activity than the silver eel, although the biochemical composition and other enzyme activities were similar. In summary, the biochemical compositions, and digestive enzymes of A. bicolor varied depending on their phases. Moreover, further studies were recommended to understand the biochemical composition of A. bicolor and digestive enzyme activity during the reproductive phase. Keywords: Anguilla bicolor, Digestive enzyme activity, Proximate analysis